2012
DOI: 10.1523/jneurosci.1487-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Astrocytes Overexpress TSPO and Are Detected by TSPO Positron Emission Tomography Imaging

Abstract: Astrocytes and microglia become reactive under most brain pathological conditions, making this neuroinflammation process a surrogate marker of neuronal dysfunction. Neuroinflammation is associated with increased levels of translocator protein 18 kDa (TSPO) and binding sites for TSPO ligands. Positron emission tomography (PET) imaging of TSPO is thus commonly used to monitor neuroinflammation in preclinical and clinical studies. It is widely considered that TSPO PET signal reveals reactive microglia, although a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
257
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 320 publications
(263 citation statements)
references
References 41 publications
6
257
0
Order By: Relevance
“…44,45 Animal studies have shown that the TSPO signal in brain is mainly derived from microglia, 20,46 with a significant contribution from astrocytes during certain conditions. 19,47 Apart from these resident immune cell populations, peripherally derived myeloid cells in the form of infiltrating or perivascular macrophages may also contribute to the signal. 45,48 In primates, systemic LPS exposure has been shown to cause a significant increase in TSPO binding within 1 to 4 hours, and postmortem immunohistochemistry confirmed a correspondence to microglia/macrophage cells, whereas colocalization of TSPO and astrocyte markers was low.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 Animal studies have shown that the TSPO signal in brain is mainly derived from microglia, 20,46 with a significant contribution from astrocytes during certain conditions. 19,47 Apart from these resident immune cell populations, peripherally derived myeloid cells in the form of infiltrating or perivascular macrophages may also contribute to the signal. 45,48 In primates, systemic LPS exposure has been shown to cause a significant increase in TSPO binding within 1 to 4 hours, and postmortem immunohistochemistry confirmed a correspondence to microglia/macrophage cells, whereas colocalization of TSPO and astrocyte markers was low.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis of TSPO in Patients With Psychosis differences between patients and control subjects (51,52). In the case of TSPO, which is expressed in microglia and astrocytes among other cells (8,9,53), autoradiographic studies have reported both higher (28) and lower (54) binding in patients as compared with HCs. Important caveats when interpreting these studies are that the age of patients and control subjects is generally high and the cause of death in patients is often suicide (52).…”
Section: Meta-analysis Of Tspo In Patients With Psychosismentioning
confidence: 99%
“…8,9 Astrocytes overexpressed vimentin in a large part of the striatum injected with lenti-CNTF (28.47 ± 4.80 mm 3 , Figure 1A). …”
Section: Lentiviral Vector-mediated Expression Of Ciliary Neurotrophicmentioning
confidence: 99%